Protection Mechanism for Solar Photovoltaic Grid (International Journal of Innovative Research in Computer Science & Technology, 2022)
Since the industrial revolution,  environmental changes have begun to affect both human  life and natural systems such as weather patterns. The  increased usage of fossil fuels since their discovery has  been blamed for this. Annual fossil fuel usage for  transportation, energy, and other sectors is projected to be  over 15 billion metric tons, resulting in harmful gases that  cause severe health im. This has resulted in a significant  push for alternative energy sources like wind and solar.  Solar is becoming more popular since it is more  dependable than wind.. With the rise in solar systems,  protection measures are becoming more important than  ever. These protection solutions must account for a variety  of system components while enhancing redundancy, such  as safeguarding the solar panels themselves, storage  devices, and loads. This paper provides a feasible  protective mechanism for solar-photovoltaic installations  operating in island mode. In the conclusion, the findings  are analyzed and summarized.
Keywords: Photovoltaic Cell; Protection; Loads